1998
DOI: 10.1159/000045091
|View full text |Cite
|
Sign up to set email alerts
|

Nonrelated Living-Donor Kidney Transplantation: Medical and Ethical Aspects

Abstract: Several patients with end-stage renal disease went to Bombay for renal transplantation from nonrelated living donors and then returned to Turkey for posttransplantation follow-up. The aims of this study are to evaluate the long-term results of renal transplantation from nonrelated living donors in Turkish patients with end-stage renal disease and to discuss the ethical and social aspects of nonrelated kidney donation. One hundred and twenty-seven patients (89 males, 38 females; mean age 38.1, range 17–63 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
(15 reference statements)
0
5
0
1
Order By: Relevance
“…Similar results also stemmed from studies from Saudi Arabia [ 11 ], Iran [ 12 , 13 ], and Republic of Korea [ 14 ]. However, studies from Turkey [ 15 , 16 ] and Pakistan [ 17 ] showed inferior rates of patient and graft survival with high rates of complications. Table 4 summarises the graft and patient survival between commercialised and noncommercialised transplants in studies with >100 patients in the last twenty years.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results also stemmed from studies from Saudi Arabia [ 11 ], Iran [ 12 , 13 ], and Republic of Korea [ 14 ]. However, studies from Turkey [ 15 , 16 ] and Pakistan [ 17 ] showed inferior rates of patient and graft survival with high rates of complications. Table 4 summarises the graft and patient survival between commercialised and noncommercialised transplants in studies with >100 patients in the last twenty years.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42] In some studies, mostly those based on small data sets, patient survival and graft survival rates are considerably lower than the internationally accepted standard; in other studies, they are shown to be comparable with local results. Confounding factors -e.g.…”
Section: Consequences and Effectsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41] Moreover, one study from the United Kingdom reports that patients who had been suspended from the local transplant list for medical reasons were operated on abroad. 33 These factors seem to indicate the existence of substandard medical practices.…”
Section: Consequences and Effectsmentioning
confidence: 99%
“…However, uteruses are sourced from donors who no longer wish to childbear and, therefore, have exhausted their function. Nevertheless, living donations are fraught with the potential for commercial sale of organs . This concern is highlighted by the appearance of the subtheme of black market trade (nonmaleficence) in our results.…”
Section: Discussionmentioning
confidence: 76%